PERAN KOMUNIKASI EFEKTIF DALAM MENINGKATKAN PRODUKTIVITAS ORGANISASI LEMBAGA PENDIDIKAN ISLAM - Ramadina, Evy; Fuadi, Imam; Mutohar, Prim Masrokan (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study examines the role of effective communication by school principals in increasing the productivity of educational institutions, particularly Islamic educational institutions. Communication is a fundamental element of organizational culture and directly influences the success of program implementation, decision-making, and the performance of all school members. Various communication barriers, such as misinterpretation of messages, one-way communication patterns, and inconsistencies in meaning, are the main causes of organizational failure in achieving goals. In the context of Islamic education, the communication characteristics of an ideal leader refer to the example of the Prophet Muhammad, including gentleness, moderation, tolerance, forgiveness, deliberation, and commitment. These characteristics have been shown to improve interpersonal relationships, create a positive school climate, and support student character development. The productivity of educational institutions is influenced by various factors such as teacher competence, leadership, infrastructure, organizational culture, and financial management. Effective communication is a connecting factor that ensures all these components work synergistically.